1996
DOI: 10.1021/jo952204h
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the Reactivities of Titanium Enolates on How They Are Generated:  Diastereoselective Coupling of Phenylacetic Acid Esters Using Titanium Tetrachloride

Abstract: Oxidative coupling of phenylacetic acid esters was easily achieved by treating the esters with TiCl(4) and then adding Et(3)N to the resulting solution. The products consisted of dl- and meso-2,3-diphenylsuccinic acid esters with the Claisen condensation product, and the ratio of these products depended on the reaction conditions. Reaction conditions suitable for high dl selectivity were determined, and a dimer of titanium enolate was postulated as an intermediate responsible for the high dl selectivity. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…In addition to this divergent result, we also found that the 1 H NMR spectra (Figures S2–S4) of the isolated compounds 3b / 4b , inexplicably, do not completely match those reported 9b. Furthermore, the formation of 5b and 6 is in agreement with the literature data10 concerning the radical dimerization or the Claisen condensation of phenylacetic ester 1b promoted by TiCl 4 /TEA 15…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…In addition to this divergent result, we also found that the 1 H NMR spectra (Figures S2–S4) of the isolated compounds 3b / 4b , inexplicably, do not completely match those reported 9b. Furthermore, the formation of 5b and 6 is in agreement with the literature data10 concerning the radical dimerization or the Claisen condensation of phenylacetic ester 1b promoted by TiCl 4 /TEA 15…”
Section: Resultssupporting
confidence: 67%
“…The synthesis of these compounds through the addition of an ester enolate4 or silyl ketene acetal5 to an imine has received special attention because of the possibility to address the reaction stereoselectivity. By these Mannich‐like reactions, several α‐alkyl‐, α‐unsubstituted‐, and α‐phenyl‐β‐aryl‐β‐amino acids have been accessed, [5c,5d,5f,6–9] whereas compounds containing α‐aryl substituents different from phenyl have not yet been prepared, owing to the easy radical dimerization of the starting arylacetic esters 10. With few exceptions,6a,6b,7a a syn / anti mixture of β 2,3 ‐amino esters forms through this method, and the syn adduct is the major diastereoisomer.…”
Section: Introductionmentioning
confidence: 99%
“…A similar chelation model was also presented in the oxidative homocoupling of ester enolates using TiCl 4 to explain the dl-selectivity. 11 In conclusion, dl-selective oxidative coupling of (Z)-boron enolate was demonstrated to give the corresponding 2,3disubstituted 1,4-diketone in a high yield. (Z)-boron enolate was prepared by 1,4-hydroboration of the enone, and it was used for the oxidative coupling reaction in one pot.…”
mentioning
confidence: 83%
“…The racemic 2,3-diphenylsuccinic acid was synthesized following a reported procedure. 28 2.2 Procedure for the synthesis of chiral macrocyclic amine (4)…”
Section: Materials Methods and Instrumentsmentioning
confidence: 99%